Pemenuhan Sarana dan Prasarana bagi Masyarakat Berkebutuhan Khusus untuk Meningkatkan Kualitas Pelayanan Publik di Daerah: (Provision of Facilities for People with Special Needs to Improve the Quality of Public Services in the Regions) - Ricky Noor Permadi; Wildan Lutfie Arieyasmieta; Rustan Amarullah (Department of Public Administration, Universitas Negeri Surabaya, 2021)
This study aims to analyze to what extent the provision of the rights of special needs groups has been implemented and provide recommendations related to the additional infrastructure outside the regulation of the Ministry of State Apparatus Utilization and Bureaucratic Reform (PANRB) Number 17 of 2017. This study is vital since the government institutions still lack attention to fulfilling the rights of persons with disabilities. In accordance with the mandate of Law Number. 25 of 2009 concerning Public Services, public service providers are obliged to provide special facilities and infrastructure for special needs groups without any additional charge. The research method used in this research is descriptive qualitative by analyzing the existing literature (library research). Then data collection through field observations (observations), interviews, and other library sources. This study tries to look at the completeness of special facilities and infrastructure for people with special needs that are provided by recommending twenty-two standards for infrastructure intended for “people with special needs”. Some public service providers relatively have almost met the standards. However, there are also public service providers which still need to be encouraged to meet these standards. It is necessary to have the political will of regional leaders to prioritize the provision of facilities and infrastructure to support public services for people with special needs. Amid limited regional resources, prioritizing the stages of fulfilment (road map) of these special facilities needs to be prepared, and partnerships also collaborations with other strategic partners can be developed to help meet these special service standards. There are limitations in this research: only three public service providers are the locus of the study, including hospitals, the Department of Population and Civil Registration, and the Department of Investment and the One-Stop Service, so that it does not represent the condition of public services in a city. Abstrak Tujuan penelitian ini adalah untuk menganalisis sejauh mana pemenuhan hak-hak kelompok berkebutuhan khusus telah diimplementasikan dan memberikan rekomendasi terkait dengan sarana-prasarana tambahan di luar peraturan Kementerian PANRB Nomor 17 Tahun 2017. Penelitian ini penting untuk dilakukan karena masih kurangnya perhatian lembaga pemerintah dalam hal pemenuhan hak-hak penyandang disabilitas. Sesuai pasal 29 UU No. 25 Tahun 2009 bahwa penyelenggara pelayanan publik berkewajiban menyediakan sarana dan prasarana khusus bagi masyarakat berkebutuhan khusus tanpa pembebanan biaya tambahan. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Pengumpulan data dilakukan melalui pengamatan lapangan, wawancara, dan sumber pustaka. Hasil penelitian menggambarkan kondisi sarana dan prasarana khusus bagi masyarakat berkebutuhan khusus yang disediakan dengan merekomendasikan dua puluh dua standar sarana prasarana bagi masyarakat berkebutuhan khusus. Beberapa penyedia pelayanan publik relatif sudah memenuhi sarana prasarana tersebut. Namun, juga terdapat penyedia layanan publik yang perlu didorong untuk memenuhi standar pelayanan khusus tersebut. Untuk memenuhi standar pelayanan bagi kelompok rentan, diperlukan political will pemimpin daerah untuk turut memprioritaskan penyediaan sarana dan prasarana penunjang pelayanan publik bagi masyarakat berkebutuhan khusus. Di tengah keterbatasan sumberdaya daerah, maka pengutamaan tahapan pemenuhan (road map) fasilitas khusus tersebut perlu disiapkan, serta pola-pola kemitraan dan kolaborasi dengan mitra strategis lainnya dapat dikembangkan untuk membantu memenuhi standar pelayanan khusus tersebut. Keterbatasan penelitian ini yaitu hanya mencakup tiga penyelenggara pelayanan publik, yang meliputi RSUD, Dinas Kependudukan dan Pencatatan Sipil dan Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu sehingga tidak menggambarkan kondisi pelayanan publik suatu daerah. Kata Kunci: pelayanan publik, aksesibilitas, berkebutuhan khusus, fasilitas, infrastruktur